Spiritual Resilience in Youth: Psychological Analysis through a Cognitive-Behavioral Approach - Frisca Elisabeth Londo; Yohan Brek; Militia C.Karin Pay; Shinta Christina (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
Youth face complex psychosocial challenges amid rapid social, economic, and technological changes. One key strategy for addressing these challenges is strengthening resilience, particularly spiritual resilience. Spiritual resilience refers to an individual’s ability to endure and recover from life’s difficulties through the power of faith, life meaning, and spiritual values. This study aims to examine the concept of spiritual resilience in youth through a cognitive-behavioral psychology (CBT) approach using a literature review method. The analysis draws upon various scholarly sources that explore the relationship between CBT mechanisms and the development of spirituality. The findings indicate that integrating CBT with spiritual values, including within a Christian context, can enhance youth’s mental endurance, assist in restructuring negative cognitions, and support mental health and spiritual growth. This approach offers a holistic and contextual intervention framework to help youth more effectively cope with stress, anxiety, and identity crises.